2013
DOI: 10.3389/fncir.2013.00189
|View full text |Cite
|
Sign up to set email alerts
|

Primate cerebellar granule cells exhibit a tonic GABAAR conductance that is not affected by alcohol: a possible cellular substrate of the low level of response phenotype

Abstract: In many rodent brain regions, alcohol increases vesicular release of GABA, resulting in an increase in the frequency of spontaneous inhibitory postsynaptic currents (sIPSCs) and the magnitude of tonic GABAA receptor (GABAAR) currents. A neglected issue in translating the rodent literature to humans is the possibility that phylogenetic differences alter the actions of alcohol. To address this issue we made voltage-clamp recordings from granule cells (GCs) in cerebellar slices from the non-human primate (NHP), M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 69 publications
4
27
0
Order By: Relevance
“…Methods for preparation of brain slices and subsequent patch‐clamp recording were similar to our previous reports in rodents and modifications for brain tissue from larger mammals . Upon removal of the brain, the frontal pole (anterior to section 0600 in the online Michigan State University sheep brain atlas: https://www.msu.edu/~brains/brains/sheep/index.html) of one hemisphere of the forebrain was rapidly isolated and immersed in an ice‐cold slurry (0–2°C) of low‐sodium artificial cerebrospinal fluid (aCSF) composed of (in millimolars) 220 sucrose, 3.2 KCl, 1.2 NaH 2 PO 4 , 6.0 MgSO 4 , 10 D‐glucose, 26 NaHCO 3 , and 0.2 CaCl 2 that was bubbled for 30 minutes with 95%O 2 /5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Methods for preparation of brain slices and subsequent patch‐clamp recording were similar to our previous reports in rodents and modifications for brain tissue from larger mammals . Upon removal of the brain, the frontal pole (anterior to section 0600 in the online Michigan State University sheep brain atlas: https://www.msu.edu/~brains/brains/sheep/index.html) of one hemisphere of the forebrain was rapidly isolated and immersed in an ice‐cold slurry (0–2°C) of low‐sodium artificial cerebrospinal fluid (aCSF) composed of (in millimolars) 220 sucrose, 3.2 KCl, 1.2 NaH 2 PO 4 , 6.0 MgSO 4 , 10 D‐glucose, 26 NaHCO 3 , and 0.2 CaCl 2 that was bubbled for 30 minutes with 95%O 2 /5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…that are a source of uncontrolled variance in clinical populations. Studies of one such model (Grant et al, 2008; Vivian et al, 2001) have demonstrated functional and genomic consequences throughout the brain following 15 months of chronic daily drinking (Acosta et al, 2010; Ariwodola et al, 2003; Budygin et al, 2003; Carden et al, 2006; Cuzon Carlson et al, 2011; Floyd et al, 2004; Grant et al, 2008; Hemby et al, 2006; Mohr et al, 2013; Welsh et al, 2011). Recently, graph theoretical analyses of fMRI data from this model found that chronic heavy drinking altered RS brain network organization (Telesford et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebellar granule cells (GCs) are key targets through which EtOH differentially affects cerebellar processing in high‐ and low‐EtOH‐consuming phenotypes (Kaplan et al., ; Mohr et al., ). GCs are the main relay of afferent information through the cerebellar cortex to Purkinje cells (PCs), the primary integrator and sole output of the cerebellar cortex.…”
mentioning
confidence: 99%
“…Specifically, while it is well established that EtOH increases the frequency of GC sIPSCs and the magnitude of the GC tonic GABA A R current in low‐EtOH‐consuming Sprague Dawley (SD) rats and DBA/2J (D2) mice (Carta et al., ; Hanchar et al., ; Kaplan et al., ), we recently determined that in high‐EtOH‐consuming C57BL/6J (B6) mice, EtOH has little impact on GC sIPSCs, and actually suppresses GC tonic GABA A R currents (Kaplan et al., ). EtOH has intermediate impact on GC sIPSCs and tonic GABA A R currents in rodents and non human primates that exhibit intermediate EtOH consumption phenotypes (Kaplan et al., ; Mohr et al., ). Importantly, with respect to cerebellar contributions to the LLR and EtOH consumption, B6 mice are significantly less sensitive to EtOH‐induced disruption of rotarod performance when compared to D2 mice (Gallaher et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation